Preparation of nano-MgO using ultrasonic method and its characteristics - Tang, Zhen-Xing; Shi, Lu-E (Eclética Química, 2008)
MgO is an important inorganic material, which can be used in many aspects, such as catalyst, toxic-waste remediation agent, adsorbent, and others. In order to make use of MgO, nano-MgO was prepared by ultrasonic method using Mg (CH3COO)2.2H2O as precursor, NaOH aqueous solution as precipitant in this paper. Effect factors on MgO nano-particle size were investigated. Characteristics of samples were measured by TGA, XRD, TEM, and others techniques. The results showed that the size of nano-MgO about 4 nm could be obtained under the following conditions (ultrasonic time 20 min, ultrasonic power 250 W, titration rate of NaOH 0.25 mL/min, NaOH concentration 0.48 mol/L, calcinations temperature 410 °C, calcination time 1.5 h, heating rate of calcination 5 °C/min). It was a very simple and effective method to prepare nano-MgO.